MEREKONTRUKSI BALE SIPON MENJADI “LITTLE UBUD” : Potensi Dan Peluang Pengembangannya - Yoyok Antoni; Ayu Gardenia Lantang (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2026)
The purpose of this research was to determine the potential and opportunities of Bale Sipon as an alternative "Little Ubud" tourist destination in Sedau Narmada. Furthermore, the Location Quotient (LQ), Specialization Index, and Shift Share calculations were used to analyze these potential and opportunities. This research was quantitative and descriptive. This quantitative research was based on the Specialization Index, Location Quotient (LQ), and Shift Share calculations, analyzing the results using GRDP and employment data. The results showed that the LQ value was greater than 1, indicating a basic sector, meaning the region has a comparative advantage and can export its products or services outside the region. Meanwhile, a Specialization Index value approaching 0 indicates that the region's economic structure is similar or not significantly specialized compared to the comparison region. The distribution of economic activities tends to be even. And the Shift Share value indicates a leading sector with high competitiveness (LQ > 1; positive Differential Shift, namely the agricultural sector in a broad sense, processing industry, electricity and gas, water supply, construction, wholesale trade and others, transportation and warehousing, provision of accommodation, food and beverages, information and communication, company services, health services and social activities and other services. In general, for tourism development in West Lombok, based on the LQ analysis, specialization index and shift share can be carried out, especially the opportunities and development of Bale Sipon in the Sedau tourist village, by paying attention to issues of accessibility, amenities, attractions, stakeholder involvement (government and community) and universities.